2021
DOI: 10.1371/journal.pone.0251084
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection and its determinants among HIV positive pregnant women: Multicenter unmatched case-control study

Abstract: Background Hepatitis B virus (HBV) kills millions of people globally; it is worse in pregnant women. HBV and Human Immune Virus (HIV) co-infection is associated with increased liver diseases such as cirrhosis and hepatocellular carcinoma. This study aimed at identifying the determinants of HBV infection among HIV-positive pregnant women. Methods A multicentre unmatched case-control study was conducted among 109 cases (HBV/HIV co-infected) and 327 controls (HIV positive) pregnant women in seven hospitals of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…This research is in accordance with the research done by Anteneh and colleagiues where after univariate analysis, the results revealed no relationship between level of education and the Hepatitis B virus infection in HIV/AIDS patients pregnant women with pvalue of 0.39 (p-value=0.39) and OR=4.2, this results implies no relationship among Hepatitis B virus infected individuals who are also ©2022, JEKK, All Right Reserved Infected with HIV/AIDS in pregnant women in Ethiopia 16 .…”
Section: Level Of Educationsupporting
confidence: 89%
“…This research is in accordance with the research done by Anteneh and colleagiues where after univariate analysis, the results revealed no relationship between level of education and the Hepatitis B virus infection in HIV/AIDS patients pregnant women with pvalue of 0.39 (p-value=0.39) and OR=4.2, this results implies no relationship among Hepatitis B virus infected individuals who are also ©2022, JEKK, All Right Reserved Infected with HIV/AIDS in pregnant women in Ethiopia 16 .…”
Section: Level Of Educationsupporting
confidence: 89%
“…Similarly, a study conducted in Nigeria noted that sexually active adults with STIs are at high risk of acquiring Hepatitis B viral infections [17]. Agrawal et al and Govindan et al found a lower prevalence of HBV among patients infected with syphilis [18, 19], other studies have noted a high prevalence of syphilis, HIV, HCV and Hepatitis B co-infection [20, 21, 22, 23, 24, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“… 44 A recent study revealed that pregnant women with HBV infection had a threefold increased risk for anemia compared with those with human immune virus‐positive status but without HBV infection. 45 One large cohort study has found a strong association between HBV infection and incident thrombocytopenia. 46 Early detection of hepatitis B virus infection before pregnancy should be considered in clinical practice, and cautious surveillance must be performed.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the presence of anemia in patients with HBV infection could indicate alterations in liver function 44 . A recent study revealed that pregnant women with HBV infection had a threefold increased risk for anemia compared with those with human immune virus‐positive status but without HBV infection 45 . One large cohort study has found a strong association between HBV infection and incident thrombocytopenia 46 .…”
Section: Discussionmentioning
confidence: 99%